Comparison of a sMBR and a CASP system for wastewater reclamation and re-use - Hasar, H; Kinaci, C (Ma Healthcare Ltd, 2004)
The performance of a submerged membrane bioreactor (sMBR) for municipal wastewater reclamation and re-use was compared with that of a current classic activated sludge process (CASP). The average chemical oxygen demand (COO) of CASP effluent was 75 mg/l, while the average COD of sMBR filtrate was 15 mg/l. In general, COD removal was above 98%. However, the best results were obtained at a sludge rentention time (SRT) of 50 days. The total phosphorus (TP) content of the filtrate decreased to a level <1 mg/l under aerobic conditions in which aeration occurred continuously. It was shown that the filtrate TIP and orthoposphate (Orto-P) concentrations increased dramatically during the periods of intermittent aeration because phosphorus is released under anoxic conditions. In the CASP effluent, the average TP and Orto-P were 7.9 mg/l and 7.1 mg/l, respectively. The filtrate was free of suspended solids (SS) and total coliform bacteria. The effluent SS in the CASP was 40 mg/l. The turbidity removal in the sMBR reached almost 99%, i.e. generally less than 1 NTU, while the average turbidity of the CASP effluent was almost 15 NTU. The removal of ammonium nitrogen (NH4+-N) in the sMBR was almost 99.8%. In addition, the nitrate concentration in the filtrate decreased to 2.4 mg/l under both aerobic & anoxic conditions. It was shown that both nitrification and denitrification could be successfully reduced through intermittent aeration. Average total Kjeldehl nitrogen (TKN) and NH4+-N in the CASP effluent were 30.2 mg/l and 20 mg/l, respectively, i.e. the nitrification efficiency was 42.9%, and the denitrification value was not available. When these results are compared with those in the CASP it indicated that the sMBR could be successfully used for reclamation and re-use of municipal wastewater.
Keywords: Activated-Sludge Process; Membrane Bioreactor; Filtration; Separation; Industrial; Aeration